Anthocyanins from Pomegranate (Punica granatum L.) and Their Role in Antioxidant Capacities in Vitro. Issue 10 (16th September 2021) - Zhao, Xueqing; Yuan, Zhaohe
Abstract: As phytochemicals, anthocyanins are not only responsible for the diverse colors in nature, but are associated with broad‐spectrum health‐promoting effects for human beings. Pomegranate is abundant in anthocyanins which possess high antioxidant capacities. However, the pomegranate anthocyanins profile and their contributions to antioxidant capacities are not fully depicted. The purpose of this article is to review anthocyanins from pomegranate as important antioxidants. Total anthocyanin content (TAC) and six major components vary greatly with intrinsic and extrinsic factors. In pomegranate, anthocyanins mainly acted as primary antioxidants, while their action as secondary antioxidants were not conclusive. The antioxidant potentials of anthocyanins were significantly affected by factors especially chemical structure and detection assays in vitro . The current knowledge may provide insights into potential applications for pomegranate anthocyanins based on their antioxidant activities. Abstract :